2016
DOI: 10.1111/avj.12529
|View full text |Cite
|
Sign up to set email alerts
|

Atypical scrapie in Australia

Abstract: The distinctive lesion profile of atypical scrapie in these five sheep highlights the diagnostic importance of routine histological evaluation of the cerebellum for evidence of neuropil vacuolation and associated PrP deposition in adult sheep with suspected neurological disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
1
19
2
Order By: Relevance
“…In addition to its potential role in the initial emergence of c-BSE in cattle, the presence of c-BSE prions in natural cases of AS has current and direct implications for both the continued risk of this ovine prion disease to other farmed animals and for human exposure risks. The distribution of AS cases are widespread across the world (17)(18)(19). A recent retrospective analysis of surveillance data collected over a period exceeding 10 y in the European Union (EU) concluded that the prevalence of detected AS cases has remained relatively stable in the different member states, with between 2 and 6 positive cases per 10,000 tested animals per year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its potential role in the initial emergence of c-BSE in cattle, the presence of c-BSE prions in natural cases of AS has current and direct implications for both the continued risk of this ovine prion disease to other farmed animals and for human exposure risks. The distribution of AS cases are widespread across the world (17)(18)(19). A recent retrospective analysis of surveillance data collected over a period exceeding 10 y in the European Union (EU) concluded that the prevalence of detected AS cases has remained relatively stable in the different member states, with between 2 and 6 positive cases per 10,000 tested animals per year.…”
Section: Discussionmentioning
confidence: 99%
“…Since its original discovery in 1998 in Norway, AS has been identified in most EU member states, in Asia, and in North and South America (17). AS has also been detected in Australia and New Zealand, 2 countries that were believed to be free of animal TSEs (18,19). Retrospective studies carried out in archived animal tissues identified an AS case in a sheep that died in 1972 in the United Kingdom, demonstrating that the disease has been present in small ruminant populations for many decades (20).…”
Section: Significancementioning
confidence: 99%
“…The National Transmissible Spongiform Encephalopathy Surveillance program includes passive surveillance for scrapie by histology for any sheep that have progressive neurological signs. A report includes the neurohistological appearance of five sheep that were found to have atypical scrapie between 1999 and 2016 . Atypical scrapie appears to be a spontaneous disease that has a similar histological appearance to the commonest of the human prion diseases.…”
Section: Production Animalsmentioning
confidence: 99%
“…A report includes the neurohistological appearance of five sheep that were found to have atypical scrapie between 1999 and 2016. 3 Atypical scrapie appears to be a spontaneous disease that has a similar histological appearance to the commonest of the human prion diseases. Histological screening for scrapie focusses on the caudal brainstem and the authors note the importance of the OIE recommendations that the cerebellum also be included in any histological screening, in order to distinguish between the two types of the disease.…”
Section: Production Animalsmentioning
confidence: 99%
“…Recently, cases of atypical scrapie were confirmed in both Australia and New Zealand, casting serious doubt on the validity of one of the most popular arguments used to reject the zoonotic potential of small ruminant prion diseases . More generally, active surveillance programs for TSE in small ruminants revealed how inaccurate knowledge was on the prevalence and geographical distribution of TSEs in small ruminants , and highlighted the limited value of past epidemiological studies aiming at assessing the zoonotic potential of animal TSEs.…”
Section: Zoonotic Potential Of Classical and Atypical Scrapiementioning
confidence: 99%